Interactions of linezolid and second-line anti-tuberculosis agents against multidrug-resistant Mycobacterium tuberculosis in vitro and in vivo. (November 2016) - Zhao, Weijie; Zheng, Meiqin; Wang, Bin; Mu, Xiaopan; Li, Peng; Fu, Lei; Liu, Shuo; Guo, Zhenyong
Graphical abstract: Highlights: The interactions of linezolid and other second-line anti-tuberculosis drugs in susceptible strains and multidrug-resistant clinical isolates in vitro were evaluated for the first time. The results of the in vitro experiments were verified in a murine tuberculosis model. A partial synergy effect was found between linezolid and capreomycin, and the combination was effective against Mycobacterium tuberculosis . The results obtained in the in vitro experiments must be verified through in vivo experiments. Summary: Objectives: The objectives of this study were to evaluate the interactions between linezolid (LZD) and second-line anti-tuberculosis (TB) agents in susceptible and multidrug-resistant (MDR) TB in vitro, and to validate the in vitro results in a murine TB model. Methods: The minimum inhibitory concentrations of LZD and seven second-line anti-TB drugs against H37Rv and three multidrug-resistant clinical isolates were determined by Alamar Blue assay, and the interaction patterns of LZD and the seven second-line anti-TB agents against the four isolates were studied using a dynamic checkerboard method. The activities of these combinations against Mycobacterium tuberculosis were evaluated in a murine model of TB. Results: The combination of LZD + capreomycin exhibited partial synergism for three of four isolates, LZD + para-aminosalicylic acid exhibited partial synergism for two of four isolates, and LZD + levofloxacin and LZD + amikacin exhibited partial synergism for one of four isolates; all other combinations showed indifference or an additive effect in vitro. The activities of six combinations and the standard regimen rifampicin + isoniazid + pyrazinamide were investigated in a murine model of TB (infection with H37Rv). Significant reductions in colony-forming units (CFU) were found in LZD + capreomycin and LZD + clofazimine groups when the CFU in the lungs on day 0 (the day of beginning treatment) was compared with the CFU in the lungs after 2 months of treatment. Conclusions: These combinations of LZD and second-line anti-TB drugs were all active against MDR-TB with indifference or an additive effect, except LZD + capreomycin, which showed partial synergy.